2008
DOI: 10.1051/parasite/2008153191
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for elucidating the phylogeny of the Apicomplexa

Abstract: Summary :The Apicomplexa is traditionally considered to contain four clearly defined groups, but the phylogenetic relationships among these groups, and their subsequent taxonomic arrangement, are currently unclear. Here, I consider five of the important criteria that need to be met before radical taxonomic changes are made, in relation to phylogenetic analyses. Unfortunately, at least four of these criteria indicate that the prospects for elucidating the phylogeny and taxonomy of the Apicomplexa are not good i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…A comparison of the coccidian parasites in anadromous and landlocked fish demonstrated that the predominant coccidian in both forms of alewives was the same species, G. ameliae . This was supported by 100% sequence homology in the small subunit 18S ribosomal RNA gene, which has been demonstrated to be a useful gene for determination of taxonomy in apicomplexan parasites ( Morrison, 2008 ). The origin of the parasite in Lake Hopatcong cannot be verified since studies on coccidians of other freshwater species in the lake are lacking.…”
Section: Discussionmentioning
confidence: 93%
“…A comparison of the coccidian parasites in anadromous and landlocked fish demonstrated that the predominant coccidian in both forms of alewives was the same species, G. ameliae . This was supported by 100% sequence homology in the small subunit 18S ribosomal RNA gene, which has been demonstrated to be a useful gene for determination of taxonomy in apicomplexan parasites ( Morrison, 2008 ). The origin of the parasite in Lake Hopatcong cannot be verified since studies on coccidians of other freshwater species in the lake are lacking.…”
Section: Discussionmentioning
confidence: 93%
“…It is important to note in this respect that a cladogram from a single molecular sequence (Fig. 5) represents only the phylogeny of that gene, which is not necessary the phylogeny of the species; this is a frequent oversight in apicomplexan parasites (Morrison 2008). For instance, the genus Plasmodium was viewed as paraphyletic relative to the genus Haemoproteus in a mitochondrial genome phylogeny (Perkins and Schall 2002), but was monophyletic in a recent three-genome phylogeny (Martinsen et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed by Merino et al (2008) and Zhu et al (2009), a molecular identification of an enigmatic parasite named Elleipsisoma thomsoni from European moles could resolve the suspected relationship with our marsupial intraerythrocytic parasites. The field of molecular phylogenetics has a major impact on the recent improved nomenclature of apicomplexan parasites (Morrison, 2008). For example, it has provided the critical evidence for the distinct origin of avian Isospora species from Cystoisospora species, linked Atoxoplasma species with avian Isospora species, supported the position of Lankesterella and Caryospora species within eimerid coccidia and has been used to link yet unknown intranuclear parasites within coccidia (Carreno and Barta, 1999; Merino et al 2006; Innis et al 2007; Schmidt et al 2008).…”
Section: Resultsmentioning
confidence: 99%